Review Article on: 1-Methylcyclopropene (1-MCP) a Breakthrough to Delay Ripening and Extend Shelf-Life of Horticultural Crops - Abu-Goukh, Abu-Bakr Ali (University of Khartoum Journal of Agricultural Sciences, 2023)
-